Oil viscosity effects on lubricant oil film behaviour under minimum quantity lubrication - N. E. H., Zamiruddin; A. S. A., Sani; N., Rosli (IOP Publishing, 2021)
Minimum Quantity Lubrication is a great alternative to flood coolant in many perspective such as economic perspective, safety and health perspective and others. In addition, natural biodegradable oils have been widely used as lubricant oil to meet the environmental-friendly machining environment. The study of lubricant oil fundamental nature during MQL machining is highly important to really identify how the lubricant oil behaviour does affects the lubricating process. Nevertheless, the study is still scarce probably due to the complexity of experimental setup and the natural flow of the lubricant oil cannot be disrupted during the machining operation. To cater this issue, the behaviour of MQL lubricant oil was investigated so a non-intrusive method called as Laser-induced Fluorescence method is applied onto Al6061 workpiece .This research was operated by different oil viscosity represented by different oil type i.e. mixed esters oil, sunflower oil, olive oil and calophyllum inophyllum oil to analyse the lubricant oil film thickness. Overall study showed that, the average of lubricant oil film thickness were significantly decreased as the oil viscosity increased affected by the spreadability of lubricant oil onto the milled surface. At all conditions for oil viscosities, the lubricant oil film showed similar downturn trend due to rise up of built-up edge formation and chips accumulation towards the milling point. Hence, the effects of MQL system parameter on the machining performance has been clarified in details through the observation on the MQL lubricant behaviour.